Using regular expressions for mining data in large software repositories - Awang Abu Bakar, Normi Sham (IEEE, 2014)
The usage of data mining technique in collecting data from software repositories involves the extraction of both basic and value-added information from existing software repositories. Regular Expressions (Regex) provide a mechanism to select specific strings from a set of character strings. In this paper, we discuss how regular expressions are used to create a data mining tool, known as OSSGrab. We developed the mining tool using Python scripting, in combination with Regex, and as a result, the time spent on data collection can be saved significantly.